Evaluasi Keamanan dari Pengembangan Formula Nanopartikel Kurkumin pada Mencit dan Potensi Antioksidan In-VitroEvaluasi Keamanan dari Pengembangan Formula Nanopartikel Kurkumin pada Mencit dan Potensi Antioksidan In-Vitro - Ni Made Dwi Sandhiutami; Rika Sari Dewi; Sondang Khairani; Sang Ayu Made Widyadari (Fakultas Farmasi Universitas Pancasila, 2022)
Curcumin has various activities such as antioxidant, anti-inflammatory, antitumor, and antibacterial. The bioavailability of curcumin is low and needs to be optimized. The manufacture of curcumin nanoparticles with several solvents is one way to increase the bioavailability of curcumin. This study aims to examine the safety of curcumin nanoparticles through acute and subchronic toxicity tests and the antioxidant activity of the formula. Acute toxicity test was performed by OECD 425 method, using AOT425StatPgm device for the LD50. Subchronic toxicity test was carried out by OECD 407 method using 4 groups: normal, a dose of 50;100; and 200 mg/kg BW for 28 days, then evaluate body weight, clinical biochemistry, and hematology. An antioxidant activity test was carried out using DPPH. The results showed were the LD50 value of curcumin nanoparticles was>5000 mg/kg BW and the results of the subchronic toxicity test (p>0.05) did not show any significant differences in AST, ALT, BUN, creatinine, albumin, and hematology compare to the normal group. The IC50 of curcumin and curcumin nanoparticles were 118.76 µg/mL and 90.87 µg/mL, respectively. It can be concluded that curcumin nanoparticles are safe and do not affect kidney and liver function and the antioxidant activity of the curcumin nanoparticle formulation is greater than that of curcumin.